Fintech frontiers in quantum computing, fractals, and blockchain distributed ledger: Paradigm shifts and open innovation - Narcisa Roxana Mosteanu; Alessio Faccia (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Among the hot research topics, Fintech is leading the trend in terms of the newest technology applications. The relatively new emerging paradigms in various sciences, such as geometry (fractals), physics (quantum), and database systems (distributed ledger-blockchain), seem to potentially contribute to a greater shift in the framework of the finance industry, bringing also some concerns (cyber-threats). Consistent and extensive investigation of the reasonable potential impact of these new models (and their underlying technologies) is performed, and then tested through a SWOT analysis, as the main objective of this research. Threats and opportunities are always intrinsically driven by the introduction of technological advancements (revolutions). This research confirms that information availability and the increasing interconnection of crosswise applications of each discovery to the different fields of science is determining the rapid succession of revolutions identified by evident large shifts in economic paradigms. The growing computing capacity and the development of increasingly powerful predictive software are leading to a competitive, extremely dynamic, and challenging system. In this context, as shown by history, there is a high possibility of market concentration in which, however, only a few corporations-digital giants-can afford to develop these technologies, consolidating their dominance.
Keywords: 650; blockchain; cybersecurity; financial markets; fintech; fractal geometry; quantum computing